DIGITAL GLOBALIZATION AND THE TRANSFORMATION OF PERSONAL SPIRITUAL VALUES: A SOCIO-PHILOSOPHICAL PERSPECTIVE (Symposium on Natural and Applied Sciences, 2026)
Digital globalization has significantly reshaped the moral, cultural, and spiritual dimensions of contemporary society by transforming patterns of communication, knowledge production, and social interaction. This article examines the transformation of personal spiritual values under the conditions of digital globalization from a socio-philosophical perspective. It analyzes the influence of digital technologies, artificial intelligence, social media, and virtual communication on ethical consciousness, cultural identity, and individual value orientations. Particular attention is devoted to the challenges of preserving spirituality in an increasingly digital environment while balancing technological innovation with humanistic principles.
Keywords: digital globalization, spiritual values, socio-philosophical analysis, digital ethics, cultural identity, moral consciousness, digital transformation, artificial intelligence, humanistic values, digital society.